Like magic - Vickers, Elaine (Harper, 2017)
Three ten-year-old girls struggle with the complications of life--Grace's best friend has moved away, Jada hopes to find the mother she hasn't seen in years, Malia braces for the changes that are sure to come with her new baby sister. And though the girls have never met, a treasure box at the local library brings them together as they each take turns adding their own special memento to it, and like magic, true friendship is born.